2010
DOI: 10.1089/jmf.2009.0214
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Wound Healing Activity ofCarapa guianensisL. (Meliaceae) Bark Extract in Rats Using Excision, Incision, and Dead Space Wound Models

Abstract: The objective of our study is to investigate the wound healing activity of the bark extract of Carapa guianensis in rats using three different wound models. The animals were randomly divided into two groups of six each in all the models. Test group animals were treated topically with the bark extract (200 mg/kg of body weight), and the controls were treated with petroleum jelly in the excision wound model. In the incision and dead space wound models the test group animals were treated with the extract of C. gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 16 publications
1
16
0
2
Order By: Relevance
“…In another study, conducted on patients subjected to inguinal hair removal with pulsed light, the oil emulsion has induced analgesic and anti-inflammatory effects comparable to those of desonide alone [38]. The wound healing activities of the ethanolic extracts of leaves and bark have been observed in studies on rats [39,40].…”
Section: Dermatologic and Cosmetic Usesmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, conducted on patients subjected to inguinal hair removal with pulsed light, the oil emulsion has induced analgesic and anti-inflammatory effects comparable to those of desonide alone [38]. The wound healing activities of the ethanolic extracts of leaves and bark have been observed in studies on rats [39,40].…”
Section: Dermatologic and Cosmetic Usesmentioning
confidence: 99%
“…Seed oil Wound healing, insect repellent, anti-psoriasis [36] Seed oil Emollient, hydrating, firming, depigmenting, rejuvenating [42] Seed oil Glucose-6-phosphate dehydrogenase inhibition [43] Seed oil/desonide emulsion Burn healing, analgesic, anti-inflammatory [37,38] Leaf ethanolic extract Wound healing [39,40] Limonoids Lenitive [42] …”
Section: Attalea Speciosamentioning
confidence: 99%
“…Many studies have reported the pharmacological properties of products obtained from the andiroba flower [1,2] , from the ethanolic extract of the andiroba leaf [3,4] and especially products derived from andiroba seed oil [5][6][7] . Andiroba oil is widely used in popular medicine in the Amazon basin region.…”
Section: Introductionmentioning
confidence: 99%
“…Andiroba oil also contains triterpenes, tetraterpenes, alkaloids, and glycerides [9] . Andiroba seed oil is currently considered to be acaricides [10] , larvicidal against Aedes aegypti [11] , as well as being an antiplasmodial [5] , anti-inflammatory [12] , anti-allergic [7,13,14] , and also suitable for wound healing [3,4] . The ethanolic extract of Carapa guianensis leaves was evaluated for antibacterial and wound healing activity, using excision, incision, and dead space wound models in rats.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional process of extracting oil from the seeds of andiroba begins with the collection and selection of them, cooking for 1-3 h in water, kneading the seeds and placing the dough in sloping surface and leaving the oil drip 18 . In this oil we highlight the anti-inflammatory activity, antiparasitic, repellents, healing activity, anti-allergic, anti-toxic at the immature stage of mosquitoes Aedes aegypti 8,22,26 . The aim of this study is to analyze the healing effect of hydro alcoholic extract of aroeira and andiroba oil via orogastric in gastrorraphies in rats, through histological and tensiometric analysis.…”
Section: Introductionmentioning
confidence: 99%